Profil Perawatan Karies Gigi pada Anak Usia 0-18 Tahun di Poli Gigi dan Mulut Rumah Sakit Umum Daerah Abdoel Wahab Sjahranie Periode 2018–2021: The Dental Caries Treatment Profile Among Children Aged 0-18 Years at the Dental and Oral Polyclinic of Abdoel Wahab Sjahranie Regional Public Hospital During the Period of 2018-2021 - Vitta Anzelia Triyana; Nydia Hanan; Musnar Munir (Jurnal Sains dan Kesehatan, 2023)
According to the 2018 National Basic Health Research (Riskesdas) Report, dental health statistics for East Kalimantan Province indicated that merely 13.8% of the population received dental care from dental healthcare professionals. Children are susceptible to developing dental caries as a result of their frequent consumption of cariogenic foods. The present investigation employs an observational approach with a descriptive research design. The sampling method utilized in this study was purposive sampling. The study population comprised of pediatric patients aged 0- 18 years who received treatment at the Dental and Oral Polyclinic of Abdoel Wahab Sjahranie Regional Public Hospital from 2018 to 2021. The total number of participants included in the study was 847. The findings of this investigation suggest that the predominant therapeutic intervention administered to individuals between the ages of 0 and 18 years is root canal therapy, with a higher frequency of treatment observed among female subjects. The lower right quadrant is the dental region that is most commonly subjected to caries treatment. Keywords:          Dental carries treatment, Teeth, Children   Abstrak Data kesehatan gigi Provinsi Kalimantan Timur di Laporan Riskesdas 2018 mengemukakan bahwa prevalensi penduduk yang menerima perawatan gigi dari tenaga medis gigi di Kalimantan Timur adalah sebanyak 13,8%. Karies gigi rentan terjadi pada usia anak-anak karena banyaknya konsumsi makanan kariogenik. Penelitian ini bersifat observasional dengan desain penelitian deskriptif dan teknik pengambilan sampel secara purposive sampling. Sampel penelitian ini adalah seluruh pasien anak berusia 0–18 tahun di Poli Gigi dan Mulut Rumah Sakit Umum Daerah Abdoel Wahab Sjahranie pada tahun 2018–2021 sebanyak 847 sampel. Hasil penelitian ini menunjukkan bahwa perawatan yang banyak diterima anak usia 0–18 tahun adalah perawatan saluran akar, jenis kelamin yang paling banyak menerima perawatan adalah pasien perempuan, dan regio gigi yang paling sering mendapatkan perawatan karies adalah regio kanan bawah. Kata Kunci:         Perawatan Karies, Gigi, Anak